2020
DOI: 10.3390/ijms21124558
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils: Underestimated Players in the Pathogenesis of Multiple Sclerosis (MS)

Abstract: Neutrophils are the most abundant circulating and first-responding innate myeloid cells and have so far been underestimated in the context of multiple sclerosis (MS). MS is the most frequent, immune-mediated, inflammatory disease of the central nervous system. MS is treatable but not curable and its cause(s) and pathogenesis remain elusive. The involvement of neutrophils in MS pathogenesis has been suggested by the use of preclinical animal disease models, as well as on the basis of patient sample analysis. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 171 publications
1
74
0
Order By: Relevance
“…The exact pathophysiological mechanism that underpins the relationship between NLR and first line treatment failure in this study is unclear. Neutrophils are an essential part of the early inflammatory cascade, and contribute to breakdown of the blood-brain barrier ( 24 , 25 ). We hypothesize that dysregulated innate immune activation, increased circulating neutrophils and sequestration of lymphocytes are indicative of a heightened inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…The exact pathophysiological mechanism that underpins the relationship between NLR and first line treatment failure in this study is unclear. Neutrophils are an essential part of the early inflammatory cascade, and contribute to breakdown of the blood-brain barrier ( 24 , 25 ). We hypothesize that dysregulated innate immune activation, increased circulating neutrophils and sequestration of lymphocytes are indicative of a heightened inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…10 Accordingly, CRP serves as a biomarker of disease activity in other immune-mediated disorders such as Crohn's disease 11 and rheumatoid arthritis. 12 The differential count of white blood cells is widely used as a marker of systemic inflammation and infection, and a recent review article suggested that neutrophils and their phenotypes potentially can be linked to specific disease courses of MS. 13 However, NLR seems to better reflect systemic inflammation compared with the specific counts for neutrophils and lymphocytes alone. NLR is calculated as the ratio of neutrophil-to-lymphocyte count, which makes it a simple, rapid, non-specific, and inexpensive way of detecting increased systemic inflammation.…”
Section: Several Biomarkers Of Inflammation Have Been Extensivelymentioning
confidence: 99%
“…Although the influx of inflammatory cells was not completely prevented by vaccination with pMOG-PEG20, total hematopoietic cells were significantly reduced to approximately 1/3. Notably macrophages and neutrophils that have both been implicated in pathology of MS (Mishra and Yong, 2016; De Bondt et al, 2020) were strongly reduced. This underlines the protective effects of pMOG-PEG20 vaccination recorded in the clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%